CONTRIBUCIÓN DE LOS MAGNONES A LAS PROPIEDADES TERMICAS DE LOS BOROCARBETOS - Vento F., J. (2005)
Using a phenomenological spin hamiltonian we calculate magnetic and thennal properties in the antíferromagnetic phase which is present in a series ofborocarbides RNí2B2C (R = Gd, Ho): the :frequency co(k) and density of states of the spin wave excitations the specific heat cv(T, H) and the mean :field Néel temperature . TN. The model has three parameters: J¡, J2 and Ha, the ferromagnetic (FM) in-plane exchange interactiot1 between first neighbors, the inter-plane antiferromagnetic (AF) exchange interaction and the anísotropic (magnetic) field. Our numerical and analitical are results ingood agreement with, respectivaly, experiments.